Toward Transformative Inclusivity through Learner-Driven and Instructor-Facilitated Writing Support: An Innovative Approach to Empowering English Language Learners - Khoo, Elaine; Huo, Xiangying (Discourse and Writing/Rédactologie)

(untitled) (Canadian Association for the Study of Discourse and Writing, 2022)
English Language Learners (ELLs) have long been targets for linguicism (i.e., linguistic racism) as they are often subjected to judgement based on deficit models of language proficiency. To support ELLs during the COVID-19 pandemic, a long-running, co-curricular writing support program based on a Learner-Driven, Instructor-Facilitated (LeD-InF) approach was modified for fully online participation. Through this approach, ELLs develop academic reading, writing, and critical thinking skills, using their respective course materials and personalized responses from their writing instructors who provide inclusive learning opportunities that specifically address ELLs’ unique individual needs. This innovative anti-deficit, proactive, and risk-free approach not only increased learners’ willingness to write and volume of written output in their academic journal entries (objectively tracked through word count), but also developed learner identity, agency, autonomy, as well as confidence. Analysis of written output volume combined with learners’ end-of-program reflections provide pedagogical insights for addressing and redressing deficit models as well as combating linguicism, contributing important steps toward ensuring equity, justice, and transformative inclusivity so that diverse voices can be heard in the teaching and learning space.